The category of case from the aspect of the axiological pragmalinguistics (on the base of Ukrainian and Russian languages) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The potential of the grammatical meaning (GM) of case as a morphological means of the expression of estimation in Contemporary Ukrainian and Russian languages are characterised in the article.
Keywords: grammatical meaning of case; estimation; Ukrainian language; Russian language